The Role of Islamic Education Teachers in Preventing Bullying Behavior - Ridho, Ihsanul Musthofa; Wibowo, Muh. Kurniawan Budi; Abbas, Ngatmin (Institut Islam Mamba'ul 'Ulum Surakarta, 2026)
The research aims to investigate types of bullying behaviour, and to understand the Islamic education teachers’ role, and the obstacles in bullying prevention. Employing field research and descriptive qualitative methodology in the Islamic Junior High School Muhammadiyah Mojolaban, interviews, observations, and documentation were conducted to collect the data. While the data analysis was carried out in 4 stages: data was collected, data were reduced, data were presented, and finally, conclusions were drawn, or the data was verified. In this study, to ensure data validity, the author used a combination of techniques, namely, extended participation, persistence, and triangulation. The results of the study were that the types of bullying done by students of SMP Muhammadiyah Mojolaban can be categorized into three types: verbal bullying, physical bullying, and relational bullying. 2) From the educational impact assessment, the role of the Islamic Religious Education (PAI) Teacher in tackling bullying behaviours at Muhammadiyah Middle School constituted the provision of educational services or socialization of the consequences of bullying, and the provision of counselling for students. 3) The positive elements supporting the PAI Teacher in the application of Religious Values, the PAI content of the teaching curriculum is abundant with Moral and Spiritual Values, and the adverse effects of the use of technology.